Electrolyte solution, electrochemical device, and electronic device
By adjusting the ratio of the second and third components in the electrolyte, and optimizing the electrolyte structure of the lithium metal battery, the problem of poor circulation and storage performance of lithium metal batteries at high temperatures is solved, a more stable and uniform SEI film is achieved, and the high-temperature performance of the battery is improved.
Patent Information
- Application Number
- CN202510120697.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-18
AI Technical Summary
Existing electrolytes are difficult to meet the needs of long cycle and low-high-temperature storage performance of lithium metal batteries at high temperatures, resulting in increased high-temperature cycle impedance and poor storage performance of the batteries.
An electrolyte is provided, including a first component, a second component, a third component and a lithium salt. By adjusting the ratio of the second component and the third component (1.5≤b/a≤10), the solvation structure of the electrolyte is optimized, the side reaction with lithium metal is reduced, and the stability and uniformity of the SEI film are improved.
This electrolyte significantly suppresses the impedance growth of high-temperature cycles in lithium metal batteries, improves high-temperature storage performance, and extends the battery's cycle life.
Smart Images

Figure CN119852529A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical energy storage, and in particular to an electrolyte, an electrochemical device using the electrolyte, and an electronic device using the electrochemical device. Background Art
[0002] Lithium metal batteries are considered to be the next generation of battery systems because they have a much higher energy density than traditional lithium-ion batteries. However, there is still no electrolyte that can simultaneously meet the requirements of high-temperature long cycle and low-temperature storage performance of lithium metal batteries. Summary of the invention
[0003] The present application provides an electrolyte, an electrochemical device and an electronic device, which can improve the impedance growth and high-temperature storage performance of a lithium metal battery during high-temperature cycling.
[0004] In a first aspect, the present application provides an electrolyte, comprising a first component, a second component, a third component and a lithium salt, wherein the first component comprises a compound represented by formula (I): (I), R1 is selected from C1 to C4 alkylene and C1 to C4 haloalkylene; R2 and R3 are each independently selected from C1 to C 10 Alkyl and C1 to C 10 A haloalkyl group; the second component includes a compound represented by formula (II) (II), R4 is selected from C1 to C4 alkylene; the third component includes at least one of a fluorinated ether compound, a fluorinated aromatic compound or a fluorinated alkane compound; the lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; wherein, based on the mass of the electrolyte, the mass proportion of the second component is a, the mass proportion of the third component is b, and 1.5≤b / a≤10.
[0005] In the present application, the electrolyte containing lithium salt, the first component and the third component has good room temperature cycle performance in the lithium metal battery. Adding the second component to the electrolyte and controlling the ratio of the second component to the third component to meet a specific range is conducive to obtaining an optimized electrolyte solvation structure and reducing the side reactions between the electrolyte components and lithium metal. At the same time, the second component can also participate in film formation, improve the stability and uniformity of the SEI film at the lithium metal interface, thereby inhibiting the impedance growth of the lithium metal battery during high temperature cycling and improving the high temperature storage performance of the lithium metal battery.
[0006] Based on the first aspect, in some embodiments, 5%≤a≤30%. When the lithium metal battery is cycled at high temperature, the stability and uniformity of the high temperature cycle interface SEI film can be optimized, thereby further improving the high temperature cycle impedance growth and high temperature storage performance of the lithium metal battery.
[0007] Based on the first aspect, in some embodiments, 10%≤b≤60%, which is conducive to obtaining an electrolyte with higher ionic conductivity and lower viscosity, and can inhibit the decomposition of the first component, cooperate with the lithium salt and the second component to form a stable and uniform SEI film during high-temperature cycling, and further improve the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery.
[0008] Based on the first aspect, in some embodiments, based on the mass of the electrolyte, the mass proportion of the first component is c, 15%≤c≤60%. This is conducive to obtaining an electrolyte with higher ionic conductivity and lower viscosity, and forming a stable and uniform SEI film during high-temperature cycling, further improving the high-temperature cycle impedance growth and high-temperature storage performance of lithium metal batteries.
[0009] Based on the first aspect, in some embodiments, based on the mass of the electrolyte, the mass proportion of the lithium salt is d, 15%≤d≤60%. This is conducive to obtaining an electrolyte with higher ionic conductivity and lower viscosity, and forming a stable and uniform SEI film dominated by lithium salt decomposition during high-temperature cycling, further improving the high-temperature cycling impedance growth and high-temperature storage performance of lithium metal batteries.
[0010] Based on the first aspect, in some embodiments, 0.5≤d / c≤2.5. This is beneficial to further optimize the ionic conductivity and viscosity of the electrolyte, facilitate the formation of a stable and uniform SEI film of the lithium metal battery at high temperature, promote the uniform and dense deposition of lithium metal, and improve the high temperature cycle performance and high temperature storage performance of the lithium metal battery.
[0011] Based on the first aspect, in some embodiments, 2≤b / a≤5. This is beneficial to further improve the impedance growth and high temperature storage performance of lithium metal batteries during high temperature cycling.
[0012] Based on the first aspect, in some embodiments, the first component includes at least one of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dipropyl ether, ethylene glycol dibutyl ether, ethylene glycol methyl ethyl ether, 1,2-propylene glycol dimethyl ether, 1,3-propylene glycol dimethyl ether and dimethoxymethane. The above substances have good room temperature cycle performance in lithium metal batteries, and are also beneficial to regulating the ionic conductivity and viscosity of the electrolyte, and form a stable and uniform SEI film at high temperatures of lithium metal batteries, which is beneficial to improving the high temperature cycle impedance growth and high temperature storage performance of lithium metal batteries.
[0013] Based on the first aspect, in some embodiments, the second component includes at least one of the compounds represented by formula (II-1) to formula (II-11): (II-1), (II-2), (II-3), (II-4), (II-5), (II-6) (II-7), (II-8), (II-9), (II-10), (II-11). The above substances can all optimize the stability and uniformity of the SEI film at the interface during high-temperature cycling of the lithium-metal battery, thereby further improving the high-temperature cycling impedance growth and high-temperature storage performance of the lithium-metal battery.
[0014] Based on the first aspect, in some embodiments, the third component includes at least one of the compounds represented by formula (III-1) to formula (III-14): (III-1), (III-2), (III-3), (III-4), (III-5), (III-6), (III-7), (III-8), (III-9), (III-10), (III-11), (III-12), (III-13), (III-14). It is beneficial to obtain an electrolyte with higher ionic conductivity and lower viscosity, and cooperate with the lithium salt and the second component to form a stable and uniform SEI film during high-temperature cycling, further improving the high-temperature cycling impedance growth and high-temperature storage performance of the lithium-metal battery.
[0015] Based on the first aspect, in some embodiments, the electrolyte further includes a fourth component, and the fourth component includes the compound represented by formula (IV): (IV), R5 is selected from H, C1 to C 10 alkyl and halo C1 to C 10 alkyl; R6 is selected from C1 to C 10 alkyl and halo C1 to C 10 alkyl; based on the mass of the electrolyte, the mass ratio of the fourth component is e, 0.5% < e < 5%. In the electrolyte containing the compound of formula (IV), the compound of formula (IV) can cooperate with the lithium salt, the first component, the second component and the third component to further improve the stability and uniformity of the SEI film formed by the lithium-metal battery at high temperature, thereby further improving the high-temperature cycling and high-temperature storage performance of the lithium-metal battery.
[0016] Based on the first aspect, in some embodiments, the fourth component includes at least one of the compounds represented by formula (IV-1) to formula (IV-18): (IV-1), (IV-2), (IV-3), (IV-4), (IV-5), (IV-6), (IV-7), (IV-8), (IV-9), (IV-10), (IV-11), (IV-12), (IV-13), (IV-14), (IV-15), (IV-16), (IV-17), (IV-18). The above compounds can improve the high temperature cycle and high temperature storage performance of lithium metal batteries.
[0017] Based on the first aspect, in some embodiments, the electrolyte further includes lithium difluorooxalatoborate (LiDFOB), and based on the mass of the electrolyte, the mass proportion of lithium difluorooxalatoborate is f, satisfying 0.2%≤f≤5%. It can cooperate with other components to further improve the SEI film formation of lithium metal batteries at high temperatures, and improve the high temperature cycle and high temperature storage performance of lithium metal batteries.
[0018] The second aspect of the present application provides an electrochemical device, which further includes a negative electrode plate and an electrolyte, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on the surface of the negative electrode current collector, wherein the negative electrode material layer is selected from at least one of lithium metal or lithium alloy; and the lithium alloy includes at least one of lithium tin, lithium zinc, lithium aluminum, lithium magnesium, lithium silver, lithium gold, lithium gallium, lithium indium, lithium platinum, lithium boron, lithium carbon or lithium silicon alloy. It can improve the high temperature cycle impedance growth and high temperature storage performance of lithium metal batteries.
[0019] Based on the second aspect, in some embodiments, the thickness of the negative electrode material layer is X μm, and the mass ratio of the lithium salt based on the mass of the electrolyte is d, and d and X satisfy: 0.003≤d / X≤0.043. The high-rate cycle performance and expansion performance of the lithium metal battery can be further improved.
[0020] The third aspect of the present application provides an electronic device, including an electrochemical device. The electrochemical device includes the electrolyte, which is beneficial to improving the high-temperature cycle impedance growth and high-temperature storage performance of the electrochemical device, thereby improving the cycle life and high-temperature storage performance of the electronic device. DETAILED DESCRIPTION
[0021] The technical scheme in the embodiment of the present application is described clearly and in detail below. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all the embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0022] An embodiment of the present application provides an electrochemical device, which includes a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.
[0023] The outer shell may be a packaging bag encapsulated by a packaging film (such as an aluminum-plastic film), for example, the electrochemical device is a soft-pack battery.
[0024] The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet. The electrode assembly may be a laminated structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet and then winding them.
[0025] Positive electrode There is no particular limitation on the positive electrode sheet in the present application, as long as the purpose of the present application can be achieved. The positive electrode sheet generally comprises a positive current collector and a positive active material. The above-mentioned positive current collector is not particularly limited, and may be any positive current collector known in the art, such as copper foil, aluminum foil, aluminum alloy foil, and composite current collector. The above-mentioned positive active material is not particularly limited, and may be any positive active material of the prior art, for example, it may include at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, or lithium iron manganese phosphate.
[0026] In the present application, the thickness of the positive electrode current collector and the positive electrode active material is not particularly limited as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 8 μm to 12 μm, and the thickness of the positive electrode active material is 30 μm to 120 μm.
[0027] In the present application, the positive electrode material layer may also include a conductive agent, and the present application has no particular restrictions on the conductive agent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of conductive carbon black (SuperP), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials or conductive polymers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.
[0028] In the present application, the positive electrode active material layer may also include a binder. There is no particular limitation on the binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon, etc.
[0029] Optionally, the positive electrode may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a commonly used conductive layer in the art, for example, including but not limited to the above conductive agent and the above binder.
[0030] Negative electrode The negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The negative electrode material layer is selected from at least one of lithium metal or lithium alloy; the lithium alloy includes at least one of lithium tin, lithium zinc, lithium aluminum, lithium magnesium, lithium silver, lithium gold, lithium gallium, lithium indium, lithium platinum, lithium boron, lithium carbon or lithium silicon alloy. The negative electrode current collector is used to carry the negative electrode material layer and conduct current, and the shape can be a foil or a mesh. The material of the negative electrode current collector includes at least one of copper foil, titanium foil, stainless steel, carbon paper or graphene paper.
[0031] In the present application, the negative electrode active material layer may further include a conductive agent. The present application has no particular limitation on the conductive agent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of the above conductive agents.
[0032] In the present application, the negative electrode active material layer may further include a binder. The present application has no particular limitation on the binder, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of the above-mentioned binders.
[0033] Optionally, the negative electrode may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a commonly used conductive layer in the art, and may include but is not limited to the above conductive agent and the above binder.
[0034] Isolation film The material and shape of the separator used in the electrochemical device of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0035] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.
[0036] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.
[0037] The binder is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).
[0038] Electrolyte In the electrolyte of the present application, the electrolyte comprises a first component, a second component, a third component and a lithium salt, wherein the first component comprises a compound represented by formula (I): (I), R1 is selected from C1 to C4 alkylene and C1 to C4 haloalkylene; R2 and R3 are each independently selected from C1 to C 10 Alkyl and C1 to C 10 A haloalkyl group; the second component includes a compound represented by formula (II) (II), R4 is selected from C1 to C4 alkylene; the third component includes at least one of a fluorinated ether compound, a fluorinated aromatic compound or a fluorinated alkane compound; the lithium salt includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI); wherein, based on the mass of the electrolyte, the mass proportion of the second component is a, the mass proportion of the third component is b, and 1.5≤b / a≤10.
[0039] In the present application, the electrolyte containing lithium salt, the first component and the third component has good room temperature cycle performance in the lithium metal battery. Adding the second component to the electrolyte and controlling the ratio of the second component to the third component to meet a specific range is conducive to obtaining an optimized electrolyte solvation structure and reducing the side reactions between the electrolyte components and lithium metal. At the same time, the second component can also participate in film formation, improve the stability and uniformity of the SEI film at the lithium metal interface, thereby inhibiting the impedance growth of the lithium metal battery during high temperature cycling and improving the high temperature storage performance of the lithium metal battery.
[0040] If the ratio of b / a is small, such as b / a<1.5, it is not conducive to improving the stability and uniformity of the SEI film at the lithium metal interface during the high-temperature cycle of the lithium metal battery, and is not conducive to improving the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery. If the ratio of b / a is large, such as b / a>10, the ionic conductivity of the above-mentioned electrolyte of the lithium metal battery decreases, and the decomposition products of the third component increase, which is not conducive to forming a stable and uniform SEI film at the lithium metal interface, and is not conducive to improving the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery. In some embodiments, the ratio of b / a can be 1.5, 2, 2.5, 3, 4, 4.5, 5, 6, 7, 7.5, 8, 9, 9.5, 10 or any value within the range composed of any two of the above values.
[0041] In some embodiments, 2≤b / a≤5, which is beneficial to further improve the impedance growth and high temperature storage performance of lithium metal batteries during high temperature cycling.
[0042] In some embodiments, 5%≤a≤30%. When the mass proportion of the second component is within the above range, the stability and uniformity of the SEI film at the high temperature cycle interface can be optimized during the high temperature cycle of the lithium metal battery, thereby further improving the high temperature cycle impedance growth and high temperature storage performance of the lithium metal battery. If a<5%, there is no significant improvement in the stability and uniformity of the SEI film at the lithium metal interface during the high temperature cycle of the lithium metal battery, so that the effect of further improving the high temperature cycle impedance growth and high temperature storage performance of the lithium metal battery is not obvious. If a>30%, the electrolyte ion conductivity in the lithium metal battery decreases, the decomposition product of the second component increases, and there is no significant improvement in the formation of a stable and uniform SEI film at the metal interface, so that the effect of improving the high temperature cycle impedance growth and high temperature storage performance of the lithium metal battery is not obvious. In some embodiments, a can be 5%, 7%, 10%, 13%, 15%, 18%, 20%, 25%, 28%, 30% or any value within the range composed of any two of the above values.
[0043] In some embodiments, 10%≤b≤60%, the mass proportion of the third component is within the above range, which is conducive to obtaining an electrolyte with higher ionic conductivity and lower viscosity, and can inhibit the decomposition of the first component, cooperate with the lithium salt and the second component to form a stable and uniform SEI film during high temperature cycling, and further improve the high temperature cycle impedance growth and high temperature storage performance of the lithium metal battery. If b<10%, there is no obvious improvement in the ionic conductivity, viscosity and high temperature interface stability of the electrolyte, and the effect of improving the high temperature cycle impedance growth and high temperature storage performance of the lithium metal battery is not obvious; if b>60%, the ionic conductivity and viscosity of the electrolyte will be reduced, and there is no obvious improvement in the stability and uniformity of the SEI film formed by the lithium metal battery at high temperature, so as to improve the high temperature cycle impedance growth and high temperature storage performance of the lithium metal battery. In some embodiments, b can be 10%, 15%, 18%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any value within the range of any two of the above values.
[0044] In some embodiments, based on the mass of the electrolyte, the mass proportion of the first component is c, 15%≤c≤60%. The mass proportion of the first component within the above range is conducive to obtaining an electrolyte with higher ionic conductivity and lower viscosity, and forming a stable and uniform SEI film during high-temperature cycling, further improving the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery. If c<15%, the ionic conductivity of the electrolyte is low and the viscosity is high, and there is no obvious improvement in the formation of a stable and uniform SEI film for the lithium metal battery at high temperature. If c>60%, it is easy to form an unstable SEI film dominated by the decomposition product of the first component, which has no obvious effect on improving the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery. In some embodiments, c can be 15%, 18%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any value within the range composed of any two of the above values.
[0045] In some embodiments, based on the mass of the electrolyte, the mass proportion of the lithium salt is d, 15%≤d≤60%. The mass proportion of the lithium salt within the above range is conducive to obtaining an electrolyte with higher ionic conductivity and lower viscosity, and forming a stable and uniform SEI film dominated by lithium salt decomposition during high-temperature cycling, further improving the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery. If d<15%, the organic component of the lithium metal SEI film at high temperature is high, and there is no significant improvement in the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery. If d>60%, the ionic conductivity of the electrolyte will be low, the viscosity will be high, and the inorganic component in the lithium metal SEI film at high temperature will be high, which will not significantly improve the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery. In some embodiments, d can be 15%, 18%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any value within the range composed of any two of the above values.
[0046] In some embodiments, 0.5≤d / c≤2.5. Controlling the ratio of d / c within the above range is beneficial to further optimize the ionic conductivity and viscosity of the electrolyte, facilitate the formation of a stable and uniform SEI film at high temperature for lithium metal batteries, promote uniform and dense deposition of lithium metal, and improve the high temperature cycle performance and high temperature storage performance of lithium metal batteries. If d / c<0.5, there is no obvious improvement in the formation of a stable and uniform SEI film, and the effect on improving the high temperature cycle and high temperature storage performance of lithium metal batteries is not obvious; if d / c>2.5, there is no obvious improvement in the formation of an electrolyte with high ionic conductivity and low viscosity, and the uniform and dense deposition of lithium metal, and the effect on improving the high temperature cycle and high temperature storage performance of lithium metal batteries is not obvious. In some embodiments, the ratio of d / c can be 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.3, 2.5 or any value within the range composed of any two of the above values.
[0047] In the electrolyte of the present application, the local high-concentration electrolyte based on lithium salt, the first component and the third component has good room temperature cycle performance in lithium metal batteries. However, under the high-temperature cycle conditions of lithium metal batteries, the local high-concentration electrolyte is still prone to side reactions with lithium metal, which will increase the internal impedance and high-temperature storage performance of the lithium metal battery and reduce the capacity retention rate. The present application adds a second component to the local high-concentration electrolyte and controls the specific ratio of the second component and the third component, which is conducive to obtaining an optimized electrolyte solvation structure, improving the stability and uniformity of the SEI film at the lithium metal interface, thereby improving the impedance growth and high-temperature storage performance of the lithium metal battery during high-temperature cycling.
[0048] In some embodiments, the electrolyte further comprises a fourth component, the fourth component comprising a compound represented by formula (IV): (IV) R5 is selected from H, C1 to C 10 Alkyl and halogenated C1 to C 10 Alkyl; R6 is selected from C1 to C 10 Alkyl and halogenated C1 to C 10An alkyl group; based on the mass of the electrolyte, the mass fraction of the fourth component is e, where 0.5% < e < 5%. In the electrolyte containing the compound of formula (IV), the compound of formula (IV) can cooperate with the lithium salt, the first component, the second component, and the third component to further improve the stability and uniformity of the SEI film formed on the lithium metal battery at high temperatures, thereby further improving the high-temperature cycle and high-temperature storage performance of the lithium metal battery. When the mass fraction e of the fourth component is within the above range, it can further promote the improvement of the stability and uniformity of the SEI film formed by the compound of formula (IV) and other components in the electrolyte, thereby improving the high-temperature cycle and high-temperature storage performance of the lithium metal battery. If e < 0.5%, the effect of improving the high-temperature cycle and high-temperature storage performance of the lithium metal battery is not obvious. If e > 5%, there is no obvious improvement in increasing the ionic conductivity and viscosity of the electrolyte and forming a low-impedance SEI film and uniform lithium deposition, and the effect of improving the high-temperature cycle and high-temperature storage performance of the lithium metal battery is not obvious. In some embodiments, e can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any value within the range composed of any two of the above values.
[0049] In some embodiments, the fourth component includes at least one of the compounds represented by formula (IV-1) to formula (IV-18): (IV-1), (IV-2), (IV-3), (IV-4), (IV-5), (IV-6), (IV-7), (IV-8), (IV-9), (IV-10), (IV-11), (IV-12), (IV-13), (IV-14), (IV-15), (IV-16), (IV-17), (IV-18). The above compounds can all improve the high-temperature cycle and high-temperature storage performance of the lithium metal battery.
[0050] In some embodiments, the first component includes at least one of ethylene glycol dimethyl ether (DME), ethylene glycol diethyl ether (DEE), ethylene glycol dipropyl ether (DPE), ethylene glycol dibutyl ether (DBE), ethylene glycol methyl ethyl ether (MEE), 1,2-propylene glycol dimethyl ether (1,2-DMP), 1,3-propylene glycol dimethyl ether (1,3-DMP) and dimethoxymethane (DMM). The above substances of the first component have good room temperature cycle performance in lithium metal batteries, and are also beneficial for regulating the ionic conductivity and viscosity of the electrolyte, and forming a stable and uniform SEI film at high temperatures of lithium metal batteries, which is beneficial for improving the high temperature cycle impedance growth and high temperature storage performance of lithium metal batteries.
[0051] In some embodiments, the second component includes at least one of the compounds represented by formula (II-1) to formula (II-11): (II-1), (II-2), (II-3), (II-4), (II-5), (II-6) (II-7), (II-8), (II-9), (II-10), (II-11). The above substances can optimize the stability and uniformity of the SEI film at the high-temperature cycle interface of lithium metal batteries, thereby further improving the high-temperature cycle impedance growth and high-temperature storage performance of lithium metal batteries.
[0052] In some embodiments, the third component includes at least one of the compounds represented by formula (III-1) to formula (III-14): (III-1), (III-2), (III-3), (III-4), (III-5), (III-6), (III-7), (III-8), (III-9), (III-10), (III-11), (III-12), (III-13), (III-14). The electrolyte containing the above substances is conducive to obtaining an electrolyte with higher ionic conductivity and lower viscosity, and can inhibit the decomposition of the first component, cooperate with the lithium salt and the second component to form a stable and uniform SEI film during high-temperature cycling, and further improve the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery.
[0053] In some embodiments, the electrolyte further includes lithium difluorooxalate borate (LiDFOB), and based on the mass of the electrolyte, the mass proportion of lithium difluorooxalate borate (LiDFOB) is f, satisfying 0.2%≤f≤5%. The mass proportion of LiDFOB is within the above range, which can cooperate with other components to further improve the SEI film formation at high temperature of the lithium metal battery, and improve the high temperature cycle and high temperature storage performance of the lithium metal battery. If f<0.2%, the effect of LiDFOB on improving the high temperature cycle and high temperature storage performance of the lithium metal battery is not obvious. If LiDFOB>5%, the content of the decomposition product of LiDFOB is high, and there is no obvious improvement in the formation of a stable and uniform SEI film for the lithium metal battery at high temperature, and the effect on improving the high temperature cycle and high temperature storage performance of the lithium metal battery is not obvious. In some embodiments, f can be 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any value within the range composed of any two of the above values.
[0054] In some embodiments, the thickness of the negative electrode material layer is Xμm, and based on the mass of the electrolyte, the mass proportion of the lithium salt is d, and d and X satisfy: 0.003≤d / X≤0.043. The ratio of the mass content of the lithium salt to the single-sided thickness of the negative electrode active material is within the above range, which can further improve the high-rate cycle performance and expansion performance of the lithium metal battery. If d / X<0.003, the lithium salt is rapidly consumed during the high-temperature cycle process, and the effect on improving the high-temperature cycle of the lithium metal battery is not obvious; if d / X>0.043, the lithium metal is rapidly consumed during the cycle process, and the effect on improving the high-temperature cycle and high-temperature storage performance of the lithium metal battery is not obvious. In some embodiments, d / X can be 0.003, 0.004, 0.005, 0.008, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.043 or any value within the range composed of any two of the above values.
[0055] According to some embodiments of the present application, the electrochemical device of the present application includes, but is not limited to: a lithium metal battery or a sodium ion battery. In some embodiments, the electrochemical device includes a lithium metal battery.
[0056] The present application also applies electrochemical devices to electronic devices to power loads in electronic devices. The above-mentioned electrochemical device contains the electrolyte, which is beneficial to improve the impedance growth and high temperature storage performance of the high temperature cycle of the electrochemical device, thereby improving the cycle life and high temperature storage performance of the electronic device. The electronic device or device of the present application is not particularly limited. In some embodiments, the electronic device of the present application includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc.
[0057] The present application is described below by specific examples and comparative examples. Those skilled in the art should understand that the preparation methods described in the present application are only examples, and any other suitable preparation methods are within the scope of the present application.
[0058] Example 1 <Preparation of soft pack battery> (1) Preparation of positive electrode The positive electrode active material NCM811 (LiNi 0.8 Mn 0.1 Co 0.1 O2), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, N-methylpyrrolidone (NMP) is added as a solvent, and a slurry with a solid content of 75% is prepared, and the slurry is stirred under the action of a vacuum mixer until the system becomes a uniform positive electrode slurry. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm and dried at 90°C. After the above steps are completed, the single-sided coating of the positive electrode plate is completed. After that, the above steps are repeated on the other surface of the positive electrode plate to obtain a positive electrode plate coated with positive electrode active materials on both sides. After coating, the positive electrode plate is cold pressed and cut into the required specifications for standby use. After testing, the single-sided thickness of the active material layer of the positive electrode plate is 60μm, and the single-sided capacity is 4mAh / cm 2 .
[0059] (2) Preparation of negative electrode sheet A metal lithium foil is placed on one surface of a negative electrode current collector copper foil with a thickness of 8 μm, and a roller is pressed with an appropriate force to make the metal lithium and the current collector adhere to each other, thereby obtaining a negative electrode sheet with a single-sided lithium foil loaded with a thickness of 20 μm.
[0060] (3) Preparation of electrolyte In an argon atmosphere glove box with a water content of <10 ppm, the components were mixed in the proportions shown in Table 1 to form an electrolyte.
[0061] (4) Isolation film A polyethylene (PE) porous polymer with a thickness of 12 μm was used as the isolation membrane.
[0062] (5) Assembly of lithium metal batteries The positive electrode sheet and the negative electrode sheet are connected to the tabs respectively, and then stacked in the order of single-sided negative electrode sheet, separator, positive electrode sheet, separator, and single-sided negative electrode sheet, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of isolation. Then, after winding and welding the tabs, they are placed in the outer packaging foil aluminum plastic film, and the electrolyte is injected. After vacuum packaging, standing, formation, capacity testing and degassing, a lithium metal battery is obtained.
[0063] Example 2 to Example 29 The preparation methods of Examples 2 to 29 are substantially the same as those of Example 1, except that the composition and content of the remaining components in the electrolyte and the preparation parameters are recorded in Tables 1 to 5.
[0064] Example 30 to Example 32 The preparation methods of Examples 30 to 32 are substantially the same as those of Example 8, except that the thickness of the negative electrode material layer is changed. The preparation parameters are recorded in Table 5.
[0065] Comparative Example 1 to Comparative Example 3 The preparation methods of Comparative Examples 1 to 3 are substantially the same as those of Example 1, except that the composition and content of the remaining components in the electrolyte and the preparation parameters are recorded in Table 1.
[0066] The thickness of the negative electrode material layer was tested for the lithium metal batteries assembled in Examples 1 to 32 and Comparative Examples 1 to 3.
[0067] Method for measuring the thickness of the negative electrode material layer: The lithium metal battery was disassembled to obtain the negative electrode sheet. The cross section of the negative electrode sheet was exposed by argon ion milling (CP), and then the thickness of the single side of the negative electrode active material was observed and measured by a scanning electron microscope (SEM).
[0068] The lithium metal batteries assembled with the electrolytes prepared in the embodiments and comparative examples were subjected to normal high temperature cycle and storage tests, and the test results are recorded in Tables 1 to 5. Performance test of lithium metal battery: High temperature cycle impedance growth rate test: At 25±5℃ and normal pressure, the prepared lithium metal battery was charged to 4.3V at a constant current of 0.2C, then charged to a current of 0.05C at a constant voltage, left to stand for 5min, discharged to 2.8V at a constant current of 0.2C, and left to stand for 5min. The discharge capacity was defined as 100%DOD capacity. The lithium metal battery was then charged to 4.3V at a constant current of 0.2C, then charged to a current of 0.05C at a constant voltage, left to stand for 5min, and then discharged to 50%DOD at a constant current of 1C. The DC internal resistance was then measured by the voltage drop displayed when a 2.5C discharge current pulse was applied for 10s, and the internal resistance at this time was defined as the initial internal resistance R0.
[0069] Then move the lithium metal battery to 45±5℃ and normal pressure environment, charge it to 4.3V at 0.2C rate, then charge it to 0.05C at constant voltage, let it stand for 5min, discharge it to 2.8V at 1C rate, let it stand for 5min, this is one cycle. Then perform 100 cycles at this charge and discharge rate.
[0070] The cycled lithium metal battery is then moved to a 45±5℃, normal pressure environment, charged to 4.3V at a constant current rate of 0.2C, then charged to a current of 0.05C at a constant voltage, left to stand for 5 minutes, and discharged to 50%DOD at a constant current rate of 1C. The DC internal resistance is then measured using the voltage drop displayed when a 2.5C discharge current pulse is applied for 10 seconds, and the internal resistance at this time is defined as the initial internal resistance R1.
[0071] The calculation formula for the high temperature impedance growth rate is: high temperature impedance growth rate = (R1-R0) / R0×100%.
[0072] High temperature storage performance test: The lithium metal battery was charged to 4.3V at 0.2C constant current at 25±5℃, and to 0.05C at 4.3V. The thickness of the battery cell was measured and recorded as the initial thickness T0. The lithium metal battery was then placed in a 60±5℃ constant temperature box. After 30 days, the thickness of the battery was recorded again at this temperature and recorded as the thickness after high temperature storage T1. The battery expansion rate before and after storage was calculated as (T1-T0) / T0×100%.
[0073] Table 1 shows the test results of the examples and comparative examples. In Table 1, compared with Comparative Examples 1 to 3, in Examples 1 to 11, when the mass ratio of the second component and the third component satisfies the relationship of 1.5≤b / a≤10, the impedance growth of the high temperature cycle of the lithium metal battery is significantly suppressed, and the high temperature storage performance of the lithium metal battery is improved. Adding the second component to the electrolyte and controlling the ratio of the second component to the third component to meet a specific range is conducive to obtaining an optimized electrolyte solvation structure, reducing the side reactions between the electrolyte components and lithium metal, and the second component can also participate in film formation, improve the stability and uniformity of the SEI film at the lithium metal interface, thereby improving the impedance growth and high temperature storage performance of the lithium metal battery during high temperature cycles. And when the b / a ratio is in the range of 2≤b / a≤5, the impedance growth and high temperature storage performance of the lithium metal battery during high temperature cycles are further improved.
[0074] Table 2 In Table 2, in Examples 12 to 21, when the mass proportions of the first component, the second component, the third component, and the lithium salt are within a specific range, and the d / c ratio is within a specific range, the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery can be further improved.
[0075] Table 3 In Table 3, in Examples 22 to 24, when the electrolyte contains the fourth component and the mass proportion of the fourth component meets a specific range, the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery are further improved.
[0076] Table 4 Combined with Table 4, in Examples 25 to 27, by adding LiDFOB to the electrolyte and the mass proportion of LiDFOB satisfies a specific range, it is found that the high temperature cycle impedance growth and high temperature storage performance of the lithium metal battery are significantly improved.
[0077] In Examples 28 to 29, when the electrolyte contains the first component, the second component, the third component, the fourth component, the lithium salt and LiDFOB at the same time, the effect of improving the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery is more obvious.
[0078] Table 5 In the above Table 5, in Example 8 and Examples 30 to 32, the thickness of the negative electrode material layer is changed, and d / X is made to meet a specific range, which correspondingly improves the high-temperature cycle impedance growth and high-temperature storage performance of the lithium metal battery.
[0079] The above disclosure is only a preferred implementation mode of the present application, and certainly cannot be used to limit the present application. Therefore, equivalent changes made according to the present application are still within the scope covered by the present application.
Claims
1. An electrolyte, characterized in that: The invention comprises a first component, a second component, a third component and a lithium salt, wherein the first component comprises a compound represented by formula (I): (I) R1 is selected from C1 to C4 alkylene and C1 to C4 haloalkylene; R2 and R3 are each independently selected from C1 to C 10 Alkyl and C1 to C 10 Haloalkyl; The second component includes a compound represented by formula (II) (II) R4 is selected from C1 to C4 alkylene; The third component includes at least one of a fluorinated ether compound, a fluorinated aromatic compound or a fluorinated alkane compound; The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; Wherein, based on the mass of the electrolyte, the mass proportion of the second component is a, the mass proportion of the third component is b, and 1.5≤b / a≤10.
2. The electrolyte according to claim 1, characterized in that Based on the mass of the electrolyte, the mass proportion of the first component is c, the mass proportion of the lithium salt is d, and the electrolyte satisfies at least one of the following conditions: (1)5%≤a≤30%; (2)10%≤b≤60%; (3)15%≤c≤60%; (4)15%≤d≤60%; (5) 0.5≤d / c≤2.
5.
3. The electrolyte according to claim 1, characterized in that 2≤b / a≤5.
4. The electrolyte according to claim 1, characterized in that The electrolyte satisfies at least one of the following conditions: (1) The first component includes at least one of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dipropyl ether, ethylene glycol dibutyl ether, ethylene glycol methyl ethyl ether, 1,2-propylene glycol dimethyl ether, 1,3-propylene glycol dimethyl ether and dimethoxymethane; (2) The second component includes at least one of the compounds represented by formula (II-1) to formula (II-11): (II-1) (II-2) (II-3) (II-4) (II-5) (II-6) (II-7)、 (II-8) (II-9) (II-10) (II-11); (3) The third component includes at least one of the compounds represented by formula (III-1) to formula (III-14): (III-1)、 (III-2)、 (III-3)、 (III-4)、 (III-5)、 (III-6)、 (III-7)、 (III-8)、 (III-9)、 (III-10)、 (III-11)、 (III-12)、 (III-13)、 (III-14).
5. The electrolyte according to any one of claims 1 to 4, characterized in that The electrolyte further comprises a fourth component, wherein the fourth component comprises a compound represented by formula (IV): (IV) R5 is selected from H, C1 to C 10 Alkyl and halogenated C1 to C 10 alkyl; R6 is selected from C1 to C 10 Alkyl and halogenated C1 to C 10 alkyl; Based on the mass of the electrolyte, the mass proportion of the fourth component is e, 0.5% <e<5%。 6. The electrolyte according to claim 5, characterized in that The fourth component includes at least one of the compounds represented by formula (IV-1) to formula (IV-18): (IV-1)、 (IV-2)、 (IV-3)、 (IV-4)、 (IV-5)、 (IV-6)、 (IV-7)、 (IV-8)、 (IV-9)、 (IV-10)、 (IV-11)、 (IV-12)、 (IV-13)、 (IV-14)、 (IV-15)、 (IV-16)、 (IV-17)、 (IV-18)。 7. The electrolyte according to any one of claims 1 to 4, characterized in that The electrolyte further includes lithium difluorooxalatoborate. Based on the mass of the electrolyte, the mass proportion of the lithium difluorooxalatoborate is f, satisfying 0.2%≤f≤5%.
8. An electrochemical device comprising a negative electrode plate, characterized in that: The electrochemical device also includes an electrolyte as described in any one of claims 1 to 7, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer arranged on the surface of the negative electrode current collector, the negative electrode material layer is selected from at least one of lithium metal or lithium alloy; the lithium alloy includes at least one of lithium tin, lithium zinc, lithium aluminum, lithium magnesium, lithium silver, lithium gold, lithium gallium, lithium indium, lithium platinum, lithium boron, lithium carbon or lithium silicon alloy.
9. The electrochemical device according to claim 8, characterized in that The thickness of the negative electrode material layer is X μm. Based on the mass of the electrolyte, the mass ratio of the lithium salt is d, and d and X satisfy: 0.003≤d / X≤0.
043.
10. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 8 or 9.